Persepsi tentang Fatherless pada Mahasiswa Universitas Lambung Mangkurat: Perceptions of Fatherlessness among Students at Lambung Mangkurat University - Rizka Amalia; Muhammad Arsyad; Nina Permata Sari (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The phenomenon of fatherlessness, or the lack of paternal involvement in parenting, is a social issue that is increasingly receiving attention in Indonesia, yet remains poorly understood. This study aims to determine the percentage of Lambung Mangkurat University students' perceptions of the fatherlessness phenomenon that is prevalent on social media, by examining three perceptual factors: attention, interpretation, and knowledge. The method used was descriptive quantitative through a survey of students from the 2021-2024 intake. The sampling technique was simple random sampling. The instrument used was an online questionnaire that was analyzed using descriptive statistics. Data collection commenced with the preparation and pilot testing of the questionnaire, followed by validity and reliability tests, and then its online distribution via Google Forms. The results showed that 64% of respondents had a perception percentage influenced by the attention factor regarding fatherlessness, 60% by the interpretation factor regarding fatherlessness, and 45% by the knowledge factor regarding fatherlessness.In conclusion, the survey revealed that students have a high level of awareness regarding the importance of fathers' roles. They recognize that the absence or suboptimal role of fathers can have negative impacts, such as low self-esteem, difficulty managing emotions, and a tendency toward juvenile delinquency. This study recommends integrating fatherlessness into guidance and counseling education and developing preventive programs for adolescents, such as group guidance, classroom sessions, and school activities that involve collaboration between parents, especially fathers, and their children.